Immigration as a factor in American history - Handlin, Oscar 1915-2011 (Spectrum book. S-2., 1959)
TRACES THE HISTORY OF IMMIGRANTS DESCRIBING PROBLEMS OF ADJUSTMENT AND HIS INDISPENSABLE ROLE IN THE INDUSTRY, AGRICULTURE, POLITICS, AND CULTURAL LIFE OF AMERICA.